Knut Hamsun at the movies in transnational contexts - Lunde, Arne (Nordlit, 2009)
This historical overview examines how the literary works of Knut Hamsun have been adapted into films over the past century, from early silent cinema to the digital age. It traces how different national and transnational cinemas have appropriated the author's texts at different historical moments. Nazi propaganda minister Joseph Goebbels, for example, took a keen interest in two Third Reich adaptations of Hamsun novels (Victoria and Pan) in the 1930s. Pan remains the Hamsun novel most frequently adapted, while Henning Carlsen's 1966 pan-Scandinavian version of Hunger is arguably the artistic highpoint to date. Nations producing or co-producing Hamsun films include Norway, Sweden, Denmark, Germany, France, the Netherlands, Russia, the United States, and Canada (Guy Maddin's 1997 Twilight of the Ice Nymphs). Hamsun at the movies has shown remarkable elasticity, crossing multiple borders, and being appropriated by disparate national cinemas for surprisingly diverse ends.
Keywords: Knut Hamsun; Film adaptations; Pan; Hunger; Henning Carlsen; National cinemas; Transnational cinemas; Joseph Goebbels; Third Reich cinema; Guy Maddin; Twilight of the Ice Nymphs